Identifikasi Morfologi Gurita di Perairan Kepulauan Togean Kabupaten Tojo Una-una, Sulawesi Tengah - Nuralim Pasisingi; Tiara Septiani Lawadjo; Ivana Butolo (Cenderawasih University, 2023)
Togean Islands in Central Sulawesi, Indonesia, are famous for their tourist areas, rich in natural resource potential, and underwater attractions. Octopus is a high economic value aquatic biota in Togean Islands. This research aimed to determine the Octopus species in Togean Islands, Tojo Una-una Regency, based on their body morphology. Identification was made by noticing external characteristics, including the shape of mantles, arms, color, and hectocotylus. Observations on the morphology of octopuses found in the Togean Islands have many similarities to the characteristics of the species Octopus cyanea. In males, an organ called the hectocotylus is presented at the third arm on the right side of the body. This organ is not found in female octopuses.